Application of the Project Based Learning Learning Model for Social Sciences Subjects on Learning Outcomes in Junior High Schools - Robeth Tegar Franseno (Yayasan Insan Mulia Bima, 2024)
This study aims to determine the effect of applying the social studies project based learning model on learning outcomes at SMP Utama Wacana 8, Mesuji Timur District, Mesuji Regency. This research is an experimental research with a quantitative approach, the design used in the pre-experimental design is the One Group Pretest-Posttest Design. The population in this study were all class VIII of SMP Utama Wacana 8 with a sample of class VIII A based on purposive sampling. Data collection techniques using tests, and documentation. Try out the requirements of the instrument by testing the validity, test the reliability of the test instrument, level of difficulty, and test the ability to differentiate the questions. Analysis prerequisite test using data normality test and linearity test. Data analysis technique using t-test analysis and simple regression test. The results showed that: (1) there was an increase in student learning outcomes before the average value was 42.59 and after the average value was 58.96. (2) the t test, namely the sig (2-tailed) provisions Tcount > Ttable 0.05 which shows that there is an influence. (3) simple regression test (R Square) of 0.366 which means that the magnitude of the effect is 36.6% and the other 63.4% is influenced by other variables